Prevalence of dysmorphophobia related to dental and facial concerns among dental students in pakistan: a cross-sectional analysis - Aleen Waheed; Qazi Jawad Hayat; Muhammad Abdullah Zuhair (Annali di Stomatologia)
Introduction: Dysmorphophobia, a psychiatric condition characterized by a preoccupation with perceived physical defects, is particularly relevant in fields like dentistry, where aesthetics play a significant role. This study aimed to assess the prevalence of dysmorphophobia related to dental and facial issues among dental students in Khyber Pakhtunkhwa (KPK), Pakistan, and to explore gender differences in its frequency. Methods: A cross-sectional study was conducted from February 1 to February 14, 2024, involving 100 undergraduate dental students aged 19–23 years from three dental colleges in KPK. A self-designed questionnaire based on the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) criteria for Body Dysmorphic Disorder (BDD) was used. Data were analyzed using SPSS version 26, with descriptive statistics and chi-square tests to evaluate gender differences. Ethical approval was obtained from the institutional ethics committee, and participation was voluntary. Results: Among the 100 students, 68% exhibited dysmorphophobic concerns, with a higher prevalence among females (73%) compared to males (61%). Emotional distress was reported by 39% of the students, and social impairment was noted in 23%. Despite reassurances from friends and family, 34% of the students remained convinced of their perceived dental defects. The majority of students (65%) reported no other significant health issues, suggesting that dysmorphophobia can occur independently. Conclusions: Dysmorphophobia is prevalent among dental students in KPK, particularly among females, and significantly impacts emotional and social functioning. Dental educators should incorporate mental health support and awareness into the curriculum to address these concerns early and ensure the well-being of future dental professionals.